2006
DOI: 10.1177/0269881106059495
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function and mood in MDMA/THC users, THC users and non-drug using controls

Abstract: Repeated ecstasy (MDMA) use is reported to impair cognition and cause increased feelings of depression and anxiety. Yet, many relevant studies have failed to control for use of drugs other than MDMA, especially marijuana (THC). To address these confounding effects we compared behavioural performance of 11 MDMA/THC users, 15 THC users and 15 non-drug users matched for age and intellect. We tested the hypothesis that reported feelings of depression and anxiety and cognitive impairment (memory, executive function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
68
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 54 publications
14
68
1
2
Order By: Relevance
“…In general, the subjects' performance increased throughout the first parts of the task but then dropped to start levels irrespective of placebo or THC treatment. The task has been repeatedly used for showing decrements in risk sensitivity in neurological, psychiatric as well as drug using populations (Bechara et al, 2001;Bolla et al, 2005;Grant et al, 2000;Lamers et al, 2005). Sensitivity of this task to acute drug effects, however, may be low as the task was never specifically designed for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the subjects' performance increased throughout the first parts of the task but then dropped to start levels irrespective of placebo or THC treatment. The task has been repeatedly used for showing decrements in risk sensitivity in neurological, psychiatric as well as drug using populations (Bechara et al, 2001;Bolla et al, 2005;Grant et al, 2000;Lamers et al, 2005). Sensitivity of this task to acute drug effects, however, may be low as the task was never specifically designed for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MDMA users made more disadvantageous choices on the IGT relative to marijuana and non-drug controls, which may be related to poor inhibitory processes (Quednow et al, 2007) and reduced white matter integrity in the anterior corpus callosum (Moeller et al, 2007). Conversely, other studies reported similar performance among MDMA users and control groups on the IGT or other decision-making tasks, although the impact of marijuana use remains unclear (Fox et al, 2002;Lamers et al, 2006). The effects of acute MDMA administration on decision-making are inconsistent and may depend on the nature of the task (Ramaekers and Kuypers, 2006;Vollenweider et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The likelihood of reporting symptoms increased with the extent of ecstasy use. Ecstasy users were also found to be significantly more depressed compared to controls in a study by McCardle, Luebbers, and Carter (2004) and more recently, Lamers, Bechara, and Rizzo (2006) found that relative to cannabis only and drug naïve controls, ecstasy/polydrug users were significantly more depressed and exhibited higher levels of anxiety. Finally, Curran, Rees, and Hoare (2004) and Hoshi, Pratt, and Mehta (2006) found that ecstasy users were more likely to attribute aggressive meanings to ambiguous sentences compared to nonusers.…”
mentioning
confidence: 90%